Integrative transcriptomic and proteomic analysis of the mutant lignocellulosic hydrolyzate‐tolerant Rhodosporidium toruloides. Issue 3 (29th March 2016) - Qi, Feng; Zhao, Xuebing; Kitahara, Yuki; Li, Tian; Ou, Xianjin; Du, Wei; Liu, Dehua; Huang, Jianzhong
Abstract : The oleaginous yeast Rhodosporidium toruloides has been considered as an economical lipid producer because it transforms carbohydrates from lignocellulosic hydrolyzate into triglycerides; however, R. toruloides cannot survive in hydrolyzate due to the inhibitors co‐produced by hydrolysis. We have previously reported a plasma mutagenesis‐generated mutant strain M18 that had strong tolerance for the stress environments of hydrolyzate. Here, we applied transcriptomic and proteomic approaches to analyze the global metabolic responses to the stress in hydrolyzate of R. toruloides and elucidate the tolerant mechanism of the mutant strain. The results showed that 57% genes matched and correlated well with their corresponding proteins. Five hundred and seven genes and 366 proteins had their transcription and expression levels changed, respectively, and 39 key genes with significantly changed transcription and expression levels (≥5‐fold changes) were identified. The results demonstrated that four cellular processes and their key genes are likely related to the mechanism of tolerance of M18 strain. Enhanced expression of the key genes in R. toruloides could improve the cellular stress tolerance to lignocellulosic hydrolyzate, while the altered expression of most key genes is probably not caused by mutagenesis, but induced by stressful environments of the hydrolyzate.